Thermomechanical Properties of a Concrete Composed of Cherry Tree Resin and Expanded Clay (Exclay) Aggregate - Bicer, Ayse; Celik, Nevin; Ozgen, Filiz; Kistak, Celal; Taskiran, Ali (Mdpi, 2024)
Expanded clay (exclay) aggregate and cherry tree resin are used in this study to produce a lightweight construction material. Based on the grain diameter, exclays are classified as d = 2-4 mm and d = 4-6 mm. Cement is added to each group as the binder material. The exclay ratios vary as 10%, 20%, 30%, 40% and 50% of the total volume in the samples. The cherry tree resin is poured into the concrete mixture with a ratio of 1% and 1.5% of cement + exclay mixture in order to form artificial pores in each sample group. The produced samples are subjected to some tests, such as thermal conductivity, water absorption and compressive strength. It is determined that due to the increase in exclay ratios and particle diameter, there is an increase in porosity along with water absorption, but there is a decrease in density, thermal conductivity and compressive strength. Hence, these newly produced concretes are recommended for panel walls, brick, concrete briquettes, inner and outer plaster and concrete partition elements.
Keywords: expanded clay aggregate; cherry tree resin; cement; light concrete